2022
DOI: 10.3389/fpls.2022.886131
|View full text |Cite
|
Sign up to set email alerts
|

LcNAC13 Is Involved in the Reactive Oxygen Species-Dependent Senescence of the Rudimentary Leaves in Litchi chinensis

Abstract: Litchi is an important evergreen fruit tree. Floral formation in litchi is induced by low temperatures (LTs). However, unstable flowering is a challenge for litchi production in times of global warming and climate change. Previous studies have shown that the methyl viologen dichloride hydrate-generated reactive oxygen species (ROS) could promote flowering. Leaves in the panicles may affect the development of the inflorescence in litchi under high-temperature condition. In this study, potted litchi trees were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that NAC transcription factors are involved in the processes of litchi rudimentary leaf senescence [68,69], fruit abscission [70], and flower bud shrinkage and abortion. Based on a bioinformatics analysis, we conducted a comprehensive analysis of the LcNAC family genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NAC transcription factors are involved in the processes of litchi rudimentary leaf senescence [68,69], fruit abscission [70], and flower bud shrinkage and abortion. Based on a bioinformatics analysis, we conducted a comprehensive analysis of the LcNAC family genes.…”
Section: Discussionmentioning
confidence: 99%